A fuzzy quadratic programming model for the design optimization of a hybrid renewable energy-water system for tropical buildings - Del Rosario, Aaron Jules R. (Animo Repository, 2019)
© 2018 IEEE. The growing global energy demand and continuous dependency on fossil fuels have triggered concerns over energy security and global warming. This issue has led to the prioritization of renewable sources in order to achieve sustainable development in the energy sector. The use of hybrid renewable sources and polygeneration systems to develop a sustainable energy system have also been emphasized in the literature. Thus, this study aims to optimize the design of a hybrid renewable energy-water system for tropical buildings. A fuzzy quadratic programming model was developed from a system architecture utilizing solar and biomass sources to meet electricity, cooling, heating, and water demands. The objective is to maximize the degree of satisfaction, which is based on multiple objectives of meeting the projected demand and minimizing the economic and environmental impacts. Technical, economic, and environmental constraints are included in the model based on fuzzy membership functions. The model was demonstrated using a case study considering a tropical commercial hotel building. The optimized system design yields a degree of satisfaction of 0.9999, compared to 0.1351 for a system with solar energy as the only source. These results highlight the benefit of renewable source hybridization and polygeneration to design a sustainable energy system.